Deletion of Kncn Does Not Affect Kinocilium and Stereocilia Bundle Morphogenesis and Mechanotransduction in Cochlear Hair Cells - Hu, Qun; Guo, Li; Li, Jie; Song, Chenmeng; Yu, Lisheng; He, David Z. Z.; Xiong, Wei (Frontiers in Molecular Neuroscience, 2018)
Auditory hair cells possess stunning cilia structure that composes of a bundle of stereocilia for mechano-electrical transduction and a single kinocilium for guiding the polarity of hair bundle towards maturation. However, the molecules underlying kinocilium function has not yet been fully understood. Hence, the proteins involved in hair bundle development and function are of a large interest. From a fine microarray analysis, we found that kinocilin (Kncn) was enriched in hair cell specific expression profile. Consistently, it has been reported that Kinocilin was a protein mainly located in the kinocilium of hair cells in the inner ear. However, the hypothesis that Kinocilin is a kinocilium protein has not been validated in mice with Kncn gene perturbed. In this study, we generated Kncn knockout mouse lines by CRISPR/Cas9 technique and further examined the morphology and function of cochlear hair cells. Our results showed that there was no obvious hearing loss in the knockout mice, determined by audiometry. Histological study demonstrated that the inner ear and hair cell structure were intact. Especially, there was no deficit of mechanotransduction in cochlear outer hair cells. In summary, our work suggests that Kinocilin is not essential for kinocilium-oriented hair bundle function in cochlear hair cells.